Elusive Destiny The Internationalist Movement in Modern Hawaii - Hooper, Paul F. (University of Hawai'i Press, 2018)
For nearly two centuries, Hawaii's leaders have endeavored to forge a unique international role for the Islands in Pacific and even in world affairs. Colorful figures such as Kalakaua, Walter Murray Gibson, and a host of others labored mightily to transform the Islands into an oceanic political power. Although their campaigns eventually failed, Hawaii was put forever on the diplomatic map with such ventures as the attempted annexation of a distant South Pacific islands group, the provocation of a quarrel with Germany that led to the brink of war, and the persistent defense of the interests of Pacific islanders in the capitals of Europe and America. A very different but nonetheless ambitious surge of activism followed Hawaii's annexation by the United States at the turn of the present century. Shortly after World War I, local internationalists formed the Pan-Pacific Union and the Institute of Pacific Relations as the foci of a concerted effort to foster greater political and cultural understanding throughout the Pacific and the world. While both groups frequently created headlines with various programs and proposals, the latter organization became widely known when it came under the attack of the anticommunist movement during the late 1940's and 1950's. Related endeavors in more recent years have produced numerous activities in educational, political, scientific, and commercial circles that presently involve a fair proportion of the Island establishment as well as numerous prominent figures from abroad. Elusive Destiny brings the details of this little-known but always present impulse in Hawaiian history together for the first time and goes on to speculate about the likely causes of successes or failures. Carefully researched and documented, richly illustrated, and concisely written, the book should interest all persons concerned with the modern Hawaiian experience.